Avaliação econômica e ambiental de ações de produção mais limpa em uma indústria de saneantes - Boff, Talia (2022)
The Chemical Industry has a large variety of processes and products, it can be considered the most diversified sector in the industrial area. Also, the Industrial Sector use to concentrate some precautions about contamination and environment impact. Commonly, large portion of this high consumption of resources results in waste and brings both environmental and economic impact for companies. In this respect, Cleaner Production emerges as a strategic management tool aimed at increasing production efficiency and reducing risks for humans and the environment. The main actions for cleaner production aim to reduce the consumption of electricity, water consumption and waste generation in the company and the subsequent evaluation of these reductions and the economic gains resulting from them. From this perspective, the general objective of the work was to carry out an economic and environmental assessment of cleaner production actions in a small sanitizer industry. The methodology includes three stages, diagnosis of the production system, proposition of cleaner production actions and putting an end to the evaluation of these actions. The diagnosis showed the production process itself, where it was possible to observe the inputs and outputs of it, soon after, the economic and environmental assessment of the proposed actions was carried out through the analysis of water and energy consumption. The evaluation resulted in a reduction of 4 m³ per month of water and 863.79 KWh per month of electricity, in addition to the economic gain of R$ 628.05 per month. The practice of Cleaner Production is focused on the implementation of techniques that in most cases do not require large investments from companies. Clean technologies combined with production processes bring several benefits to the industrial sector, as they result in cost reductions, while preserving the environment and natural resources. It is expected that the company can carry out the actions and contribute to itself and the environment.